Prediction of gas hydrate formation in the presence of methanol, ethanol, (ethylene, diethylene and triethylene) glycol thermodynamic inhibitors. (3rd August 2018) - Vatani, Zoha; Amini, Ghazale; Samadi, Mitra; Fuladgar, Amir Masoud
ABSTRACT: Hydrate formation is a serious, fundamental problem in the blocking of process equipment and pipelines in gas transportation pipelines. The objective of the present work is the simulation of the pipelines in the 15th and 16th phases of South Pars and investigation of operating conditions for hydrate formation. The effects of injecting various thermodynamic inhibitors on the hydrate formation conditions have also been studied. According to the simulation results, investigation of the operational reasons and the cost of these compounds, pure methanol and monoethylene glycol were determined as the best inhibitors for gas flow rates of 500 and 1000 mmscfd.